Arguments of Maslahah and Mafsadat in Modern Islamic Economic Law in Indonesia and Morocco - AM Hasan Ali; M. Salman Yusuf; Qosim Arsadani (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2023)
Abstract. This study analyzes the arguments for maslahah (benefit) and mafsadat (harm) in developing modern Islamic economic law in Indonesia and Morocco by exploring the practice of murabahah in banking. As this study shows, the dialogue between maslahah and mafsadat may result in the notion of emergency and needs (hajiyat) in economic activities. Using document studies, this study finds that maslahah has been used as the foundation of Islamic economic practices. These include the establishment of financial institutions, market mechanisms, hisbah institutions, and the prohibition of foreign exchange speculation. Meanwhile, maslahah al ammah is considered in using dinar and dirham in transactions. Abstrak. Penelitian ini menganalisis argumen maslahah (manfaat) dan mafsadat (kerugian) dalam pengembangan hukum ekonomi Islam modern di Indonesia dan Maroko dengan mengeksplorasi praktik murabahah di dunia perbankan. Studi ini menunjukkan bahwa dialog antara maslahah dan mafsadat dapat menghasilkan pengertian darurat (daruriyat) dan kebutuhan (hajiyat) dalam kegiatan ekonomi. Dengan menggunakan studi dokumen, penelitian ini menemukan bahwa maslahah telah digunakan sebagai landasan praktik ekonomi Islam di Indonesia dan Maroko. Hal ini mencakup pembentukan lembaga keuangan, mekanisme pasar, lembaga hisbah, dan pelarangan spekulasi valuta asing. Sementara itu, maslahah al ammah dipertimbangkan dalam penggunaan dinar dan dirham dalam transaksi